Enhancing Employee Performance through Motivation, Discipline, and Environment in Indonesia - Nur Fatma Wati; Vera Firdaus (Indonesian Journal of Law and Economics Review, 2024)
This study investigates how motivation, work discipline, and work environment impact employee performance at PT. Prima Karya Cemerlang. Using a quantitative approach with a sample of 100 production employees, data were collected through questionnaires and analyzed using multiple linear regression, t-test, F-test, and SPSS software. The results show that motivation, work discipline, and work environment each significantly affect employee performance and collectively have a simultaneous impact. These findings suggest that enhancing these factors can improve employee performance, offering strategic insights for HR management at PT. Prima Karya Cemerlang. Highlight: Impact of Motivation: Motivation significantly boosts employee performance. Role of Work Discipline: Work discipline enhances employee performance. Influence of Work Environment: Optimized work environment improves employee performance. Keyword: Employee performance, motivation, work discipline, work environment, quantitative analysis